Pengaruh Sosial Media Marketing terhadap Keputusan Pembelian Konsumen pada Coffee Shop Makecents - Yohanes Infan Doli; Agus Mariani Saragih; Desri Wiana; Jenny Sari Tarigan; Dewi Comala Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of the coffee shop business in Indonesia is now showing rapid growth. One of the cities in Indonesia that has a rapidly growing coffee shop business is Medan. With the emergence of more coffee shops, there can be more intense competition in the coffee industry, to gain this competitive advantage, one of the things that can be done is to do social media marketing. One of the coffee shops in Medan city that does social media marketing is Makecents Coffee Space, Makecents Coffee Space does social media marketing through social media Instagram, Facebook, and Tiktok to promote their products and places. This study aims to determine the effect of social media marketing on consumer purchasing decisions for Makecents coffee shop. The type of research used in this research is quantitative. The population used in this study were visitors to Makecents coffee shop. The number of respondents consisted of 100 people, with incidental sampling techniques and sample determination using the Lemeshow formula. The results showed that all social media marketing variables influenced the purchasing decisions of Makecents coffee shop consumers, which amounted to 73.5%, the remaining 26.5% was influenced by other variables not examined in this study.